ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. ASTRA OTOPARTS, TBK PERIODE TAHUN 2017-2022 - Abthar Syaifullah, Almasyah; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
This research aims to determine the financial performance of PT Astra Otoparts Tbk in the 2017-2022 period using financial ratios, namely Liquidity Ratios, Solvency Ratios, Activity Ratios and Profitability Ratios. The method used is the Quantitative Descriptive method, the type of data used by researchers is secondary data. The data obtained by researchers is time series data from the financial reports of PT Astra Otoparts. Researchers obtained company financial report data via the BEI website. The research results show that the Liquidity Ratio of PT Astra Otoparts Tbk for the 2017-2022 period shows an unhealthy condition, because the average value obtained from the Current Ratio (CR) is 168.2%, which is below the industry standard, namely 200%, Quick Ratio (QR) 102.9% is below the industry standard, namely 150%, Cash Ratio (CR) 34.5% is below the industry standard, namely 50%. The Solvency Ratio shows a healthy condition, with an average Debt to Asset Ratio (DAR) value of 31.1%, which is sufficient for the industry standard of 35%, the Debt to Equity Ratio (DER) of 47.7% is below the industry standard value of 90%. The Activity Ratio shows an unhealthy condition, with an average value of Total Asset Turnover Ratio (TATO) of 0.91 times, which is below the industry standard, namely 2 times, the Fixed Asset Turnover Ratio (FATO) is 4.3 times, which is below the industry standard, namely 5 times. . The Profitability Ratio is said to be unhealthy because it is still below industry standards. The results show an average Gross Profit Margin (GPM) of 14.4%, below the industry standard, namely 30%, Net Profit Margin (NPM) of 4.3%, which is below the industry standard, namely 20 %, Return On Assets (ROA) of 3.8% is below the industry standard of 30%, and Return On Equity (ROE) of 6.3% is below the industry standard of 40%.